2011
DOI: 10.1007/s00586-011-2020-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective therapy using granulocyte colony-stimulating factor for patients with worsening symptoms of compression myelopathy, part 1: a phase I and IIa clinical trial

Abstract: Objective Based on the neuroprotective effects of granulocyte colony-stimulating factor (G-CSF) on experimental spinal cord injury, we initiated a clinical trial that evaluated the safety and efficacy of neuroprotective therapy using G-CSF for patients with worsening symptoms of compression myelopathy. Methods We obtained informed consent from 15 patients, in whom the Japanese Orthopaedic Association (JOA) score for cervical myelopathy decreased two points or more during a recent 1-month period. G-CSF (5 or 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…6 At 1 month after the administration, he underwent surgery for decompression of the spinal cord using a posterior approach and T4-T12 posterior instrumented fusion. At 6 months after the administration, his recovery from myelopathy was maintained (JOA score = 6 points) with no recurrence of pain.…”
Section: Case Reports Casementioning
confidence: 99%
See 3 more Smart Citations
“…6 At 1 month after the administration, he underwent surgery for decompression of the spinal cord using a posterior approach and T4-T12 posterior instrumented fusion. At 6 months after the administration, his recovery from myelopathy was maintained (JOA score = 6 points) with no recurrence of pain.…”
Section: Case Reports Casementioning
confidence: 99%
“…Thus, we suggested that intravenous administration of G-CSF at a dosage of 10 μg/kg/day for 5 days is an appropriate protocol for G-CSF neuroprotective therapy. 6 During this trial, we encountered an unexpected finding -two patients in whom neuropathic pain associated with thoracic myelopathy was dramatically reduced after G-CSF administration. Such a pain-relieving effect of G-CSF had not been included as an endpoint in this trial.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present phase I/IIa trial, we administered G-CSF to 11 patients with acute SCI, and confirmed the safety of administering up to 10 lg/kg/day G-CSF. Along with the present study, we have performed another clinical trial of G-CSF neuroprotective therapy for worsening symptoms of compression myelopathy [29]. In that phase I/IIa clinical trial, we administered G-CSF (5 or 10 lg/kg/day) intravenously for 5 consecutive days to 15 patients; the results also indicated that G-CSF administration up to 10 lg/kg/ day is safe.…”
Section: Neuroprotective Therapy With G-csf For Acute Scimentioning
confidence: 75%